Lipid Extracted Microalgal Biomass Residue as a Fertilizer Substitute for Zea mays L. - Maurya, Rahulkumar; Chokshi, Kaumeel; Ghosh, Tonmoy; Trivedi, Khanjan; Pancha, Imran; Kubavat, Denish; Mishra, Sandhya; Ghosh, Arup (Frontiers in Plant Science, 2016)
High volumes of lipid extracted microalgal biomass residues (LMBRs) are expected to be produced upon commencement of biodiesel production on a large scale, thus necessitating its value addition for sustainable development. LMBRs of Chlorella variabilis and Lyngbya majuscula were employed to substitute the nitrogen content of recommended rate of fertilizer (RRF) for Zea mays L. The pot experiment comprised of 10 treatments, i.e., T1 (No fertilizer); T2 (RRF-120 N: 60 P2O5: 40 K2O kg ha−1); T3 to T6—100, 75, 50, and 25% N through LMBR of the Chlorella sp., respectively; T7 to T10—100, 75, 50, and 25% N through LMBR of Lyngbya sp., respectively. It was found that all LMBR substitution treatments were at par to RRF with respect to grain yield production. T10 gave the highest grain yield (65.16 g plant−1), which was closely followed by that (63.48 g plant−1) under T5. T10 also recorded the highest phosphorus and potassium contents in grains. T4 was markedly superior over control in terms of dry matter accumulation (DMA) as well as carbohydrate content, which was ascribed to higher pigment content and photosynthetic activity in leaves. Even though considerably lower DMA was obtained in Lyngbya treatments, which might have been due to the presence of some toxic factors, no reduction in grain yield was apparent. The length of the tassel was significantly higher in either of the LMBRs at any substitution rates over RRF, except T6 and T7. The ascorbate peroxidase activity decreased with decreasing dose of Chlorella LMBR, while all the Lyngbya LMBR treatments recorded lower activity, which were at par with each other. Among the Chlorella treatments, only T5 recorded significantly higher values of glutathione reductase activity over RRF, while the rest were at par. There were significant increases in carbohydrate and crude fat, respectively, only in T4 and T3 over RRF, while no change was observed in crude protein due to LMBR treatments. Apparently, there was no detrimental effect on soil properties, suggesting that both the LMBRs can be employed to reduce the usage of chemical fertilizers, thus promoting maize crop production in a sustainable manner.